The Phenomenon of Moving to Online/Distance Delivery as a Result of COVID-19: Exploring Initial Perceptions of Higher Education Faculty at a Rural Midwestern University - Cameron-Standerford, Abby; Menard, Katherine; Edge, Christi; Bergh, Bethney; Shayter, Ashley; Smith, Kristen; VandenAvond, Laura (Frontiers in Education, 2020)
The purpose of this study was to explore the initial perceptions and experiences of faculty whose classes were moved to an online/distance delivery as a result of the COVID-19 pandemic. Using mixed methods online survey methodology, the researchers sought to describe faculty perceptions relative to their response to moving all university courses online within the timeframe allotted by university leadership. Building upon this groups’ previous research, which focused on the relationships among care and rigor in the online teaching/learning environment, the researchers designed survey questions to further explore these concepts during a time of chaos. The survey addressed faculty perceptions and lived experiences related to supporting this transition, previous experiences with online teaching, the role of rigor and care in course design and implementation, and opportunities for demonstrating care towards colleagues. Information gleaned from the study will help to inform university leadership, instructional design support personnel, and faculty. As the long-term economic, social, and academic effects are realized across the world, the researchers anticipate significant changes in higher education.